SPRING 2002 : Jong beeldend talent in Antwerpen. - Paulus, Camille; Van Kersschaever, Jasmina; Koningin FabiolaZaal, Antwerpen (Antwerpen : [s.n.], 2002)
De Vries, Erki ; Mels, Michiel ; Ouwerkerk, Susanna ; Segers, Lieven ; Tanghe, Vladimir ; Van Buggenhout, Greetje ; Van Dromme, Robert ; Verhulst, Katrijn ; Vermeulen, Angelo ; Vlegels, Greet
SPRING 2002, Koningin FabiolaZaal, Antwerpen, van 18 april tot 17 mei
kunstcatalogus
Keywords: Antwerpen